Native and myeloperoxidase-oxidized low-density lipoproteins act in synergy to induce release of resolvin-D1 from endothelial cells. (May 2018) - Dufour, Damien; Khalil, Alia; Nuyens, Vincent; Rousseau, Alexandre; Delporte, Cédric; Noyon, Caroline; Cortese, Melissa; Reyé, Florence; Pireaux, Valérie; Nève, Jean; Vanhamme, Luc; Robaye, Bernard; et al.
Abstract: Background and aims: Oxidation of native low-density lipoproteins (LDLs-nat) plays an important role in the development of atherosclerosis. A major player in LDL-nat oxidation is myeloperoxidase (MPO), a heme enzyme present in azurophil granules of neutrophils and monocytes. MPO produces oxidized LDLs called Mox-LDLs, which cause a pro-inflammatory response in human microvascular endothelial cells (HMEC), monocyte/macrophage activation and formation of foam cells. Resolvin D1 (RvD1) is a compound derived from the metabolism of the polyunsaturated fatty acid DHA, which promotes resolution of inflammation at the ng/ml level. Methods: In the present study, we used liquid chromatography–mass spectrometry (LC-MS/MS) to investigate the synthesis of RvD1 and its precursors - 17(S)-hydroxy docosahexaenoic acid (17S-HDHA) and docosahexaenoic acid (DHA) - by HMEC, in the presence of several concentrations of Mox-LDLs, copper-oxidized-LDLs (Ox-LDLs), and native LDLs or in mouse plasma. The LC-MS/MS method has been validated and applied to cell supernatants and plasma to measure production of RvD1 and its precursors in several conditions. Results: Mox-LDLs played a significant role in the synthesis of RvD1 and 17S-HDHA from DHA compared to Ox-LDLs. Moreover, Mox-LDLs and LDLs-nat acted in synergy to produce RvD1. In addition, different correlations were found between RvD1 and M1 macrophages, age of mice or Cl-Tyr/Tyr ratio. Conclusions: These results suggest that although Mox-LDLs are known to be pro-inflammatory and deleterious in the context of atherosclerosis, they are also able to induce a pro-resolution effect by induction of RvD1 from HMEC. Finally, our data also suggest that HMEC can produce RvD1 on their own. Highlights: Myeloperoxidase (MPO)-oxidized LDLs stimulates resolvin D1 (RvD1) production by endothelial cells. Copper-oxidized LDLs are unable to stimulate RvD1 production by endothelial cells. Native-LDLs and MPO-oxidized LDLs act synergistically to induce RvD1 production. Pro-inflammatory MPO-oxidized LDLs induce also a pro-resolutive answer. PLA2 is one of the key player for RvD1 production.